Frendak to Phenis to Breivik: An Examination of the Imposed Insanity Defense - Richie, William Donald; Alam, Farzana; Gazula, Lalitha; Embrack, Harold; Nathani, Milankumar; Bailey, Rahn Kennedy (Frontiers in Psychiatry, 2014)
The imposition of the insanity defense is a complicated psycho-legal scenario. Globally, definitions of insanity differ from country to country. In a multitude of cases, a determination of insanity at the time of a criminal act means the offender will not be considered responsible for his or her action(s). In many jurisdictions, concerns have been raised that the insanity defense has been used to mitigate punishment, usually after a particularly heinous crime. In this review, the authors use three cases - FRENDAK, PHENIS, and BREIVIK to demonstrate how the imposition of the insanity defense has been used for legal purposes in the past and present. In an effort to give more background to each of the above-mentioned cases, the writers have provided some details to aid comprehension. The authors offer recommendations for the ethical forensic evaluator unburdened by partisan allegiance and invested in the search for truth. This review article relies on peer-reviewed articles available from PubMed, Meharry Online Library and legal dictionaries. We also cross-referenced reputable news sources to ensure the validity of the facts we present.